Sexually Dimorphic Expression of Fear-conditioned Analgesia in Rats and Associated Alterations in the Endocannabinoid System in the Periaqueductal Grey. (1st January 2022) - Llorente-Berzal, Alvaro; McGowan, Fiona; Gaspar, Jessica C.; Rea, Kieran; Roche, Michelle; Finn, David P.
Highlights: Male, but not female, rats expressed fear-conditioned analgesia. Expression of other fear-related behaviours was higher in males than females. Fear-related increases in periaqueductal grey (PAG) levels of OEA and GABA in male rats, but not females. Evidence for sex differences in expression of endocannabinoid-related receptors in the PAG. Abstract: The endocannabinoid system within the periaqueductal grey (PAG) has been implicated in fear-conditioned analgesia (FCA), the profound suppression of pain upon re-exposure to a context previously paired with an aversive stimulus. Since the endocannabinoid and nociceptive systems exhibit sexual dimorphism, the aim of the present study was to assess possible sex differences in the expression of FCA, fear in the presence of nociceptive tone, and associated sex-dependent alterations in the endocannabinoid system within the PAG. Male and female Sprague-Dawley rats received footshock (10 × 1s; 0.4 mA; every 60 s) or no-footshock in a conditioning arena and 23.5 h later received intraplantar injection of formalin (2.5%) under brief isoflourane anaesthetic into the right hind paw. Nociceptive and fear-related behaviours were assessed 30 min later. Levels of endocannabinoids, N -acylethanolamines and neurotransmitters in the PAG were assessed by LC–MS/MS and expression of endocannabinoid system-related proteins by Western immunoblotting. Male, but not female, rats exhibited robust FCA and greater expression of fear-related behaviours than females. Fear-conditioned formalin-treated males, but not females, had higher levels of N -oleoylethanolamine (OEA) and γ-aminobutyric acid (GABA) in the PAG, compared with non-fear-conditioned controls. There was no effect of fear conditioning on the levels of FAAH or CB1 receptor expression (CB1R) in the PAG of male or female formalin-treated rats. Non-fear-conditioned females had higher levels of CB1R and PPARγ expression than non-fear-conditioned male counterparts. In summary, our results provide evidence of sexual dimorphism in the expression of FCA and fear-related behaviours, and associated alterations in components of the endocannabinoid system and GABA within the PAG.